2001
DOI: 10.1007/s002650000314
|View full text |Cite
|
Sign up to set email alerts
|

Costs of trail construction and maintenance in the leaf-cutting ant Atta columbica

Abstract: Leaf-cutting ants of the genus Atta use trunk trails during foraging which may persist for months or years. The time and energy costs of trail construction and maintenance were estimated for colonies of Atta columbica on Barro Colorado Island, Panama, to determine if these costs are likely to constrain new trail construction and promote persistence of existing trails. Large workers 2.2-2.9 mm in headwidth participated in trail-clearing significantly more frequently than typical leaf-carriers, indicating that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 32 publications
2
82
0
1
Order By: Relevance
“…The range of headwidth and fragment size we found in the experiments with the uncovered bridge is slightly smaller (Feener et al 1988;Shutler and Mullie 1991;Burd 1995) or very similar (Howard 2001) to that found in Weld studies on Atta colombica. Moreover, the correlation between load size and maximal headwidth is similar to that found by other authors (Shutler and Mullie 1991;Burd 1996).…”
Section: ¡1supporting
confidence: 61%
“…The range of headwidth and fragment size we found in the experiments with the uncovered bridge is slightly smaller (Feener et al 1988;Shutler and Mullie 1991;Burd 1995) or very similar (Howard 2001) to that found in Weld studies on Atta colombica. Moreover, the correlation between load size and maximal headwidth is similar to that found by other authors (Shutler and Mullie 1991;Burd 1996).…”
Section: ¡1supporting
confidence: 61%
“…It remains to be seen whether, in the natural environment, trail widths are adjusted to optimize the net benefit of the trail, given the traffic demand, the cost of clearing (Howard, 2001) and the effect of traffic density on contact rates and information exchange. Indeed, according to our results, building wider foraging trails not only could be more costly but could also result in a lower foraging efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, they make physical transportation corridors as long as 200 m by cutting and clearing debris and vegetation along paths to foraging sites, and they maintain these pathways in the face of a rain of leaf litter [14]. These trails direct and restrict a colony's searching and foraging effort [15,16], so that essentially all resource movement occurs along these transportation corridors.…”
Section: Introductionmentioning
confidence: 99%
“…These trails direct and restrict a colony's searching and foraging effort [15,16], so that essentially all resource movement occurs along these transportation corridors. Trails carry the traffic of workers to and from leaf sources where ants harvest leaf tissue that is used as a substrate for their mutualist fungal gardens in the nest [14,17]. A colony's cumulative trail network used over the course of a year tends to form a highly branched pattern radiating in all directions from the central nest [18], although only one or a few minimally branching trails may be in active use on a given day.…”
Section: Introductionmentioning
confidence: 99%